IMPROVING SCIENTIFIC ARTICLE WRITING SKILL THROUGH COLLABORATIVE WRITING LEARNING TECHNIQUE - Hartati, Yulia Sri; Rasyid, Yumna (IJLECR (International Journal of Language Education and Cultural Review), 2017)
The purpose of this research is to improve scientific writing skills through collaborative learning writing techniques students of Language and Literature Education STKIP PGRI Indonesia West Sumatra. This research is an action using Elliot action model consists of seven stages, namely the identification of the first step, findings and analysis of the facts, general planning, action, action observation, evaluation of the implementation of the action, and reflection and improvement. This research was conducted in three cycles. Sources of data in this study are students Session B Language Study Program and Literature Indonesia PGRI STKIP West Sumatra, class of 2014. The data were processed qualitatively and quantitatively. The results of the study during three cycles showed an increase in the average value of scientific writing skills through collaborative learning writing techniques at the end of the test. The average value of the test in cycle 1 is 56.56. The average value of the test in cycle 2 was 69.64. The average value of the test in cycle 3 is 81 The average value of the test show that collaborative learning writing techniques can improve students’ academic writing skills.